The application of carbon nanoparticles in the lymph node biopsy of cN0 papillary thyroid carcinoma: A randomized controlled clinical trial - Xiao Fan Xu; Jun Gu (Asian Journal of Surgery, 2017)
Objective: We applied carbon nanoparticle suspensions to the papillary thyroid carcinoma cases with no clinical regional lymph node metastasis (cN0) to show the lymph flow from primary tumors, and evaluated its value in the lymph node biopsy of cN0 papillary thyroid carcinoma and protection of parathyroid. Patients and methods: One hundred and fourteen patients with cN0 papillary thyroid carcinoma were randomly assigned to experimental and control groups. The experimental group received carbon nanoparticles injection around the primary tumor, while the control group received no injection. Both groups subsequently received standard lateral thyroid gland resection, isthmus resection, subtotal thyroidectomy, or clearance of lymph nodes (LNs) of the central compartment. Results: A total of 342 LNs of the central compartment were dissected in the experimental group (6.00 ± 0.98 per patient) with 81 LNs confirmed to be positive (0.95 ± 0.77 per patient), whereas 261 LNs of the same area were dissected in the control group (4.58 ± 0.60 per patient) with 27 confirmed to be positive (0.47 ± 0.50 per patient). There is a significant difference between experimental and control groups in the average number of LNs dissected per patient (6.00 ± 0.98 vs. 4.58 ± 0.60, p < 0.001) but not the positive LNs per patient (0.95 ± 0.77 vs. 0.47± 0.50, p = 0.11). Parathyroid was found in two patients from the experimental group and in seven patients in the control group (p = 0.29). Three patients in the experimental group and seven patients in the control group had hypocalcemia (p = 0.21), and four patients in each group had hoarseness (p = 0.58). Conclusions: Carbon nanoparticle suspensions can be used to stain central lymph nodes of cN0 papillary thyroid carcinoma without staining of parathyroid and leakage, and improve the resection of LNs.